2021
DOI: 10.1111/ijcp.14850
|View full text |Cite
|
Sign up to set email alerts
|

Association between elevated brain natriuretic peptide levels and weaning failure: A systematic review and meta‐analysis

Abstract: Objective: Cardiovascular dysfunction has been reported as an important mechanism of weaning failure, and recent data suggest that elevated brain natriuretic peptide (BNP) levels is associated with an increased risk of weaning failure. Therefore, we performed this meta-analysis to evaluate the correlation between elevated BNP levels and weaning failure in critically ill patients subject to mechanical ventilation.Methods: A systematic search in Cochrane Library, Embase, PubMed and Web of Science was performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Cardiac biomarkers may be a useful tool in the evaluation of patients before and during the weaning process. Two recent pooled analyses of studies on BNP and weaning confirmed that higher levels before SBT are predictive of weaning failure [ 41 , 42 ]. In their observational study, Farghaly and coworkers measured BNP before and after 2 h of SBT.…”
Section: Monitoring the Weaning And Assessing Causes Of Sbt Failurementioning
confidence: 99%
“…Cardiac biomarkers may be a useful tool in the evaluation of patients before and during the weaning process. Two recent pooled analyses of studies on BNP and weaning confirmed that higher levels before SBT are predictive of weaning failure [ 41 , 42 ]. In their observational study, Farghaly and coworkers measured BNP before and after 2 h of SBT.…”
Section: Monitoring the Weaning And Assessing Causes Of Sbt Failurementioning
confidence: 99%